Efficacy of Nadi Shodhana, Bhramari Pranayama and Yoga Nidra on Symptoms of Premenstrual Syndrome Among Young Adult Females: A Prospective Randomized Controlled Trial - Gonmei, Lanjiklu; KV, Swathi; Shetty P S, Sharada; Shetty, Vanitha S (Indian Journal of Integrative Medicine, 2025)
Background and Objectives: Premenstrual syndrome is frequently suffered by women of reproductive age, characterized by a range of physical, emotional, and psychological symptoms, and has a detrimental impact on their mood and productivity. Female college students are especially vulnerable to this condition. Yogic practices like Nadi shodhana, and Bhramari can help in reducing stress and enhancing mental clarity, Yoga Nidra induces a state of deep relaxation, and alleviates physical discomfort and emotional turbulence. This study aimed to evaluate the impact of Nadi shodhana, Bhramari Pranayama, and Yoga Nidra in relieving the symptoms of premenstrual syndrome among young adult females. Materials and Methods: In this prospective randomized control trial, 60 female participants between age18 to 25 who fulfilled the study criteria were enrolled. Subjects were randomly divided into a study group and a control group using a lottery method. PSST and VAS were assessed before and after 8 weeks of intervention. Result: Results suggested that the experimental group demonstrated a significant reduction in the Premenstrual Symptoms Screening Tool (PSST) (p≤0.05) and Visual Analog Scale (VAS) (p≤0.05). Interestingly in the control group, there was also a significant but lesser extent reduction in the Premenstrual Symptoms Screening Tool (PSST) (p≤0.05) and Visual Analog Scale (VAS) (p≤0.05). Conclusion: The present study indicates that Nadi Shodhana, Bhramari pranayama and Yoga nidra on PMS subjects has significantly reduced PMS symptoms and severity, suggesting the cost-effective and easily accessible intervention.